The Influence of Hedonic Browsing and Flow Experience of Instagram on Food and Beverages Online Impulsive Buying - Jessica Novia Husada; Claudy Prawiyadi; Fransisca Andreani (Petra International Journal of Business Studies, 2023)
Marketers use Instagram as one of the most popular social media platforms to sell their products or services. Its features have encouraged its consumers to spend time doing hedonic browsing. This online browsing enables consumers to get a flow experience that makes them buy products and services impulsively, especially food and beverages. This study is to determine the effects of the hedonic browsing and flow experience of Instagram on food and beverages to online impulsive buying. The questionnaires were taken from 160 respondents and analyzed using SPSS and Partial Least Square (PLS). The results of this study show that hedonic browsing has a positive and significant influence on flow experience.  Flow experience has a positive and significant influence on online impulsive buying. Hedonic browsing also has a positive and significant influence on online impulsive buying. Finally, flow experience has mediated the effect of hedonic browsing on the impulsive online buying of food and beverages.